Development of Competency Framework Assessment Tool Regarding Antibiotic Prescription in Dentistry - Qaiser Ali Baig, Sualeha Abban, Muhammad Mohsin Kamal, Muhammad Usman Muneer, Momin Bin Fiaz, Maha Tanvir (Pakistan Journal of Medical & Health Sciences, 2023)
–9+ generate competency framework questionnaire for antibiotic prescriptions, assess framework of four major components including safety, professionalism, improvements, and collaborations and to find association between demographic factors and competency framework for prescription writing. Methods: the study was convenient in sampling technique, cross sectional, analytical in design which includes fresh dental graduates from Pakistani Dental Schools. A self-complete questionnaire was generated, piloted, validated and tested for reliability. Data were analyzed using SPSS. Results: The mean competency score of the sample was ten point nine eight (SD±three point three) out of a total score of nineteen. The highest score obtained was nineteen and minimum zero among individuals. The competency levels were also scored different among dental schools with few institutions scored better in all categories than other when split up in public or private sectors. Many of the house surgeons (n=237) showed command on antibiotic prescription and are also aware of antibiotic misuse. However, they consider it not feasible to prescribe via remote media (N=one hundred and ninety-four) like online prescriptions. Practical implication: This study will have a broad impact on the antibiotic prescription routine among the dentist and it will help improve to improve competency on antibiotic prescription among dental undergraduates with a framework focusing more on evidence based community practices and in line with the significance of tackling solutions for drug resistant microorganisms that can lead to more complex situations. Conclusion: It is concluded that a need is found to improve competency on antibiotic prescription among dental undergraduates with a framework focusing more on evidence based community practices Keywords: Antibiotics, antimicrobial resistance, dental curriculum, competency.